Studi Komparasi Pola Penataan Permukiman Tepian Sungai di Indonesia dengan Pendekatan Riverfront Architecture - Wardana, Thobi Yoga; Mufidah, Mufidah; Faisal, Muhammad (Universitas muhammadiyah palembang, 2023)
Rivers cannot be separated from human life, and higher population growth has caused land conversion in river-protected areas to become densely populated settlements. This conditions not only the environment but also the community itself. Therefore it is essential to study and compare the objects of riverside settlements in Indonesia so that they can become a pilot for the arrangement of riverside settlements in the future. The method used is a descriptive qualitative comparison by comparing three riverside settlement objects in Indonesia: Kampung Juminahan Yogyakarta, Kampung Code Yogyakarta, and Kampung Tongkol North Jakarta with a riverfront architecture approach. The results found that of all the objects studied, Kampung Code Yogyakarta met almost all indicators in the riverside architectural approach, including environmental, recreational, and educational functions, regardless of its advantages and disadvantages.